2007
DOI: 10.1144/0016-76492005-185
|View full text |Cite
|
Sign up to set email alerts
|

Episodic fire, runoff and deposition at the Palaeocene–Eocene boundary

Abstract: Qualitative and quantitative coal petrological analyses have been undertaken on the laminated lignite at the base of the Cobham Lignite Bed, from Scalers Hill, Kent, England. The maximum negative carbon isotope excursion, which marks the beginning of the Palaeocene-Eocene thermal maximum (PETM), occurs near the top of the laminated lignite. The lignite contains inertinite, a petrographic term used to describe charcoal. The laminated lignite has inertinite-rich and inertinite-poor layers indicative of episodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 61 publications
4
39
0
Order By: Relevance
“…8) indicative of climatic perturbation. According to Garel et al (2013), these paleohydrological changes relate to a latest Paleocene climatic event that is also recorded in England, where the emergence of a flora adapted to episodic fire is observed below the CIE (Collinson et al, 2007), and in…”
Section: Causes Of Paleofloral Changesmentioning
confidence: 91%
See 1 more Smart Citation
“…8) indicative of climatic perturbation. According to Garel et al (2013), these paleohydrological changes relate to a latest Paleocene climatic event that is also recorded in England, where the emergence of a flora adapted to episodic fire is observed below the CIE (Collinson et al, 2007), and in…”
Section: Causes Of Paleofloral Changesmentioning
confidence: 91%
“…However, local and regional changes have been detected, such as a decrease in the abundance of gymnosperms during the PETM, observed in the Arctic (Schouten et al, 2007) and in landmasses bordering the North Sea Basin (Kender et al, 2012), as well as in Wyoming (Wing et al, 2005;Smith et al, 2007). In the London Basin, the vegetation adapted to episodic fires, which characterizes the latest Paleocene, disappears after the P-E boundary (Collinson et al, 2003(Collinson et al, , 2007(Collinson et al, 2009. At lower latitudes, a decrease in diversity has been observed in the paratropical flora of America (US Gulf Coast) during the earliest Eocene (Harrington and Jaramillo, 2007), whereas the equatorial flora of eastern Colombia and western Venezuela was subjected to an increase in diversity (Jaramillo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To make the blocks, the slabs were broken down to smaller, manageable sizes, surface embedded in epoxy resin followed by vacuum treatment to prevent fragmentation (Jones and Rowe, 1999), sawn perpendicular to bedding into slices of appropriated size for reflectance analysis, and then polished using aluminum oxide powder to obtain a highly reflective surface (Collinson et al, 2007).…”
Section: Polished Block Preparationmentioning
confidence: 99%
“…Kurtz et al (2003) suggested that extensive burning of peat deposits released massive amounts of 13 C-depleted carbon (∼10 000 Gt) during the PETM. However, this would necessitate an early Paleogene peat reservoir at least 10 times the mass of the modern peat reservoir (Higgins and Schrag, 2006;Page et al, 2011), and there is no evidence for wholesale burning of peat (Collinson et al, 2007;Moore and Kurtz, 2008) or the total collapse of the biosphere in general (Jaramillo et al, 2010;McInerney and Wing, 2011).…”
Section: Other Hypotheses For Massive Carbon Inputmentioning
confidence: 99%